Analisis Konteks: Perubahan Perilaku Masyarakat Pasca Program Kota Tanpa Kumuh (KOTAKU) - Nurkhasanah Nurkhasanah; Rutiana Dwi Wahyunengseh (Jurnal Mahasiswa Wacana Publik, 2021)
City Without Slums Program (KOTAKU) is a strategic effort of the Ministry of Public Works and Public Housing to accelerate the handling of slum settlements in Indonesia. One of the program’s objectives is to provide housing infrastructure. However, no matter how much infrastructure is built, it will be in vain if there is no public awareness to care for, maintain, and change their behavior towards a clean and healthy life. This study aims to analyze the sustainability aspects of KOTAKU Program policy by studying behavior change. This study focuses on the environmental context that contributes to the change or absence of behavior change and the type of changes in community behavior after the implementation of the KOTAKU Program in Pucungrejo Village and Sokorini Village, Muntilan District, Magelang Regency. The research method used is a qualitative research method with data collection through documentation, observation, and in depth interviews. Selection of informants using purposive sampling technique. Data were analyze using interative analysis by Miles and Huberman. Furthermore, interview data were also analyzed using the Nvivo 12 Plus application. The results showed that: (1) intervention from external factors greatly contributed to change in people’s behavior; (2) changes in people’s behavior take place at the cognitive, affective, and behavioral levels; (3) the barriers to behavior change are individual characteristics of the community itself to its environment.